2021
DOI: 10.1021/acs.jpcb.1c08215
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of the [C4mim][Cl] Ionic Liquid and Its Mixtures with Water: Insight from a 1H NMR Experimental and QM/MD Study

Abstract: The 1 H NMR chemical shift of water exhibits non-monotonic dependence on the composition of an aqueous mixture of 1-butyl-3-methylimidazolium chloride, [C4mim][Cl], ionic liquid (IL). A clear minimum is observed for the 1 H NMR chemical shift at a molar fraction of the IL of 0.34. To scrutinize the molecular mechanism behind this phenomenon, extensive classical molecular dynamics simulations of [C4mim][Cl] IL and its mixtures with water were carried out. A combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…These changes to the hydrogen bonding network may also cause an increase in the viscosity at very low water content while at higher water content, the viscosity decreases. These findings are supported by Lengvinaitė et al [12], who investigated the structure of the IL with varying amounts of water via NMR. It was observed that the water forms hydrogen-bonded aggregates with the anions and that these aggregates surround the imidazolium ring cations.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…These changes to the hydrogen bonding network may also cause an increase in the viscosity at very low water content while at higher water content, the viscosity decreases. These findings are supported by Lengvinaitė et al [12], who investigated the structure of the IL with varying amounts of water via NMR. It was observed that the water forms hydrogen-bonded aggregates with the anions and that these aggregates surround the imidazolium ring cations.…”
Section: Introductionsupporting
confidence: 70%
“…The fundamental importance of the PEM to the operation of fuel cells has prompted a number of studies into the properties of IL/ water mixtures and the behaviour ILs confined in porous materials. These systems have been investigated using a broad range of experimental and computational techniques, including quasielastic neutron scattering (QENS) [7][8][9][10][11], nuclear magnetic resonance (NMR) [7,10,12], and molecular dynamics simulations (MD) [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to experimental observations, the impressive results on HB interactions in ILs and ILCs have been obtained by molecular dynamics (MD) simulations. 8,[11][12][13]16,[27][28][29][30] The MD analysis of the non-mesogenic ionic liquid C 4 mimCl indicated that Cl is strongly localized in front of the acidic hydrogens in the imidazolium group. 30 Recent modelling of this material and its mixture with water has predicted a strong hydrogen bonding interaction between the C2-H2 moiety of imidazolium and the chloride anions.…”
Section: Introductionmentioning
confidence: 99%
“…30 Recent modelling of this material and its mixture with water has predicted a strong hydrogen bonding interaction between the C2-H2 moiety of imidazolium and the chloride anions. 29 Chlorides were also found to coordinate imidazolium in the vicinity of the C4-H4 and C5-H5 bonds. In the modelling of hydrated ILs, it has been shown that water molecules acted as hydrogen-bonded links between chloride anions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation